Implementation of Ultra-Modified Symmetric Sequence Algorithm for Space Vector Modulation of Matrix Converter - Kotb B. Tawfiq; A. S. Mansour; E. E. EL-Kholy (Institute of Advanced Engineering and Science, 2018)
This paper proposes an ultra- modified symmetric sequence algoritm of space vector modulation of matrix converter. The ultra-modified technique improves the drawbacks of the modified one where it provides a reduction of the total harmonic distortion for both output voltage and output current. Some of the advantages of matrix converter are introduced in this paper. These advantages represented in the output frequency of matrix converter which may be greater than input frequency, controlling rms value of the output voltage and the ability to control the input displacement factor.At the end of this paper simulation and experimental results are introduced which give a presice proof to the proposed algorithms.